A Practical Guide to Assessment Literacy - Notar, Charles E.; Allanson, Patricia E. (Advances in Social Sciences Research Journal, 2018)
In the age of accountability, it is important for educators to understand key principles of assessment practices. Too often terms are used interchangeably. This article reviews core knowledge of assessment literacy as used within educational context. History and definition of assessment terms are provided. Tables provide examples of assessment tools and characteristics of formative and summative assessments.